Outcomes in African-American women with suspected acute myocardial infarction: the Myocardial Infarction Triage and Intervention Project. - Maynard, C. (National Medical Association, 1995)
Increasing attention has been given to the investigation of cardiovascular disease in women, although African-American women have received little attention. This study compares characteristics and outcomes in women admitted to coronary care units for suspected acute myocardial infarction (MI). Between January 1988 and December 1991, a total of 554 (5%) African-American and 9738 (95%) white women with suspected acute MI were admitted to coronary care units in metropolitan Seattle, Washington. Relevant demographic socioeconomic, clinical, and outcome data were abstracted from the medical record and entered in the Myocardial Infarction Triage and Intervention registry. African-American women were younger, more often single and unemployed, and were less likely to have health insurance than their white counterparts. In addition, a higher proportion of African-American women reported a history of hypertension and diabetes mellitus. After adjustment for age, African-American women were equally as likely to develop acute MI and were more likely to die in the hospital. In addition, a higher proportion of African-American women were readmitted to coronary care units for suspected MI. Compared with their white counterparts, African-American women with suspected acute MI were considerably worse off from both socioeconomic and clinical standpoints, and their relative disadvantage was apparent in poor outcomes.